Access to archival information: A theoretical approach of the post-custodial strand with the functional thesaurus - Alencar, Maíra Fernandes [UNESP]; Cervantes, Brígida Maria Nogueira [UNESP] (Universidade Federal da Paraíba, 2019)
Archival institutions justify their reason for existing through an essence: to provide access to information in physical or electronic documents of a particular institutional or personal body. The theories and practices surrounding this access issue have built the trajectory of archival from ancient times to the present. Considering this panorama of its essence, this article seeks to systematize a theoretical approach of the Post-Custodial Archives (theoretical section of the area that advocates the access question) with the archival information retrieval tool: Functional Thesaurus (vocabulary of organicfunctional language). The research universe consists of the scientific literature in the period from 2000 to 2016 with the terms functional thesaurus, post-custodial archival, organic-functional language and controlled archival vocabulary in the sections title, abstract and keywords of the works, in Portuguese, Spanish and English, with post-custodial archives and functional thesaurus. For the analysis of the data, the Bardin content analysis method is used, grouping in Ranganathan's PMEST categories. It was verified that the thematic of the functional thesaurus did not find in the literature scientific works within the established methodological parameter, whereas in the post-custodial archives, 12 works were recovered. It can be verified that the latter has, as energy that moves it, the terminological instruments in the prism of the access. Thus, there is an approximation of the post-custodial strand with the functional thesaurus. It was found that there is a need for studies that deepen the field of language in the perspective of access to archival information.
Acesso à informação arquivística: Uma aproximação teórica da vertente pós-custodial com o tesauro funcional
Keywords: Controlled vocabulary; Functional thesaurus; Post-custodial arquives science